ANALISIS EFESIENSI ANGGARAN DAN REALISASI BIAYA OPERASIONAL PADA CV SOLATA TRAVEL - Nely Salu Padang (JURNAL ULET (Utility, Earning and Tax), 2021)
The purpose of this study is to determine the efficiency of the budget and the realization of operational costs at CV Solata Travel. The method used is descriptive method. The data collection instrument used in this study is documentation, namely budget data and overall cost realization from 2017 – 2019 at CV Solata Travel. The data analysis instrument used is efficiency ratio analysis. The results of the data analysis that have been carried out are known that overall operational cost control at CV Solata Travel is classified as inefficient. This is due to the fact that the number of realized costs is greater than or equal to the amount of the planned budget.